Analysis of the diagnostic value of NLR and PLR in cervical lymph node metastasis of tongue squamous cell carcinoma before surgery - CHENG Longlong; ZHANG Shihan; MENG Xin; ZHANG Jingrui; ZHOU Ying; WANG Yonggong (Kouqiang hemian waike zazhi)
[Objective:] To analyze the clinical value of preoperative blood inflammatory markers in diagnosing cervical lymph node metastasis in patients with tongue squamous cell carcinoma (TSCC). [Methods:] A total of 141 TSCC patients who underwent surgical treatment in Henan Provincial People's Hospital from January 2017 to June 2023 were included. According to the postoperative pathological results, they were divided into cervical lymph node metastatic group and cervical lymph node non-metastatic group. The index of peripheral blood inflammatory cells (neutrophil, platelet, and lymphocyte count values) were collected from patients before surgery, and the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) were calculated to analyze the value of preoperative NLR and PLR in diagnosing cervical lymph node metastasis in TSCC patients. [Results:] The NLR and PLR values in cervical lymph node metastatic group were significantly higher than those in the cervical lymph node non-metastatic group. The area under the curve (AUC) and optimal cutoff values for diagnosing cervical lymph node metastasis in TSCC patients using NLR and PLR are 0.72, 2.24 and 0.61, 115.43, respectively. Multivariate logistic regression analysis showed that NLR is an independent influencing factor for cervical lymph node metastasis in TSCC patients. [Conclusion:] The preoperative inflammatory marker NLR may be a potential biomarker for evaluating cervical lymph node metastasis in TSCC patients.